Optimization of operating conditions for the application of Moringa oleifera (Zogale) seeds extract in water disinfection using response surface methodology - Bichi, Mustafa Hassan; Agunwamba, Jonah Chukwumemeka; Muyibi, Suleyman Aremu (Academic Journals, 2012)
Good quality dry seeds of Moringa oleifera were selected and the seed coat and wings were removed manually. The kernel was ground to fine powder using the coffee mill attachment of the Moulinex domestic food blender. The ground powder was then sieved through 210 μm sieve. The seed powder was de-fatted using hexane in electro-thermal Soxhlet extractor. Moringa seeds extract was obtained using the de-fatted seed cake and aqueous extraction. Different preparations of Moringa extract were added to 10 mL of the Escherichia coli suspension and incubated for 2 h without agitation. Survival of bacterial cells was assessed by making dilution series of bacterial suspensions, plating on non-selective LB medium agar dishes, and incubating for 48 h at 37°C. Duplicates were made of every individual assay. Colonies were counted on dishes and the bacterial cell survival ratio was estimated by comparison to a control experiment where no Moring extract was added. The bacterial removal was optimized by varying the mixing time, mixing speed, and Moringa seeds extract dosage. Statistical optimization was conducted by using central composite design (CCD). The experimental data was analyzed using statistical software DESIGN EXPERT, V6.4.8 DEC 10 2002 for Windows. The response surface model was used to determine the optimum operating condition that yields the highest antimicrobial compounds activities from M. oleifera seeds extracts. A cubic model was fitted to the data. The standard deviation for the cubic model was 0.56, with R2 = 0.9999 and adjusted R2 = 0.9994. The analysis of variance (ANOVA) showed that the effects of mixing time, mixing speed and Moringa dosage were significant (p < 0.05) in the extraction process. The Quadratic model was used in predicting the responses and the optimal conditions were determined as 31 min mixing time, 85 rpm mixing speed and 3.25 mg/mL Moringa dosage. The results show that the predicted and experimental values were not significantly different and it was thus concluded that the model obtained can be used to optimize the process of antimicrobial bioactive compound extraction from de-fatted M. oleifera seeds.